Camurati–engelmann disease with obesity in a newly identified family carrying a missense p.Arg156Cys mutation in the TGFB1 gene. Issue 8 (3rd July 2013) - Collet, Corinne; Laplanche, Jean‐Louis; de Vernejoul, Marie‐Christine
Abstract We report on a family affected by Camurati–Engelmann disease, characterized by radiological signs limited to the tibia, and associated with overweight or obesity, which is not a known feature of this disorder. The affected patients were heterozygous for a c.466C > T mutation (which predicts p.Arg156Cys) in the latency associated protein (LAP)‐coding domain of the TGFB1 gene. This mutation had previously been reported once in another family with a similar, atypical phenotype, which suggests a possible phenotype/genotype relationship. © 2013 Wiley Periodicals, Inc.